ADAPTIVE TRANSFORMATIONAL LEADERSHIP IN THE DIGITAL AGE: A LITERATURE REVIEW OF STRATEGIES EMPLOYED BY LEADERS OF ISLAMIC EDUCATIONAL INSTITUTIONS IN ADDRESSING CULTURAL AND TECHNOLOGICAL CHANGE - Syaiful Bahri Djamarah (CV. Adiba Aisha Amira, 2026)
The digital age presents a dual challenge for Islamic educational institutions: technological disruption and the cultural shifts of Generation Z. This literature review analyses the concept of adaptive transformational leadership as a hybrid model that integrates the four dimensions of Bass & Riggio with the adaptive principles of Heifetz et al. Key strategies include the transformation of Sharia-compliant digital infrastructure, upskilling teachers through the Google Educator Islami certification, a digital-religious literacy curriculum, Sharia-compliant gamified blended learning, and an Islamic balanced scorecard for data analytics. Findings indicate a 28–40% improvement in academic performance, strengthened digital ethics, and enhanced organisational cultural resilience within madrasahs. Strategic recommendations include digital prophetic leadership and an anti-misinformation “Islamic Cyber Patrol” to drive madrasah transformation towards Indonesia Emas 2045.